Pelatihan Penggunaan Celup Putting pada Anggota Kelompok Peternak Sapi Perah Margo Mulyo Sebagai Pencegahan Mastitis pada Sapi Perah - Merryafinola Ifani; Yusuf Subagyo; Hermawan Setyo Widodo; Rizak Tiara Yusan (Politeknik Piksi Ganesha Indonesia, 2025)
Tirto Margo Mulyo Livestock Group still practices conventional dairy cattle management with inadequate sanitation and milking hygiene management. This has led to a high incidence of mastitis, which adversely affects the farm, such as decreased milk quality and production, increased treatment costs, and accelerated culling of cows. The community service program implemented includes examinations using the California Mastitis Test, training in making disinfectant solutions, and teat dipping. This program aims to develop farmer cadres, maintain milk quality and quantity, and prevent both clinical and subclinical mastitis. The pre-test results showed an average score of 6 points among the group members. While the farmers were aware of mastitis, they were unfamiliar with subclinical mastitis. A post-test was conducted after the program, and the results showed an improvement, with the average score rising to 8 points. Additionally, the mastitis testing revealed a decrease in subclinical mastitis among the dairy cows in the Margo Mulyo group. Conclusion, the community service activities (PMM) were successful in increasing the farmers' knowledge, reducing the incidence of mastitis, and enhancing the motivation of the farmers to implement proper milking management practices.